2003
DOI: 10.1074/jbc.m211293200
|View full text |Cite
|
Sign up to set email alerts
|

Cyclosporin A Prevents the Hypoxic Adaptation by Activating Hypoxia-inducible Factor-1α Pro-564 Hydroxylation

Abstract: Cells respond to low oxygen tensions by up-regulating the expression of genes involved in angiogenesis (e.g. vascular endothelial growth factor), erythropoiesis (e.g. erythropoietin), and glycolysis. The transcriptional activation of target genes is induced by a common transcription factor, hypoxia-inducible factor-1 (HIF-1). 1 HIF-1 was first identified as a heterodimeric transactivator that recognizes a specific DNA sequence, termed hypoxia-responsive element (HRE) in the 3Ј-untranslated region of the erythr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
2
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(63 citation statements)
references
References 27 publications
4
56
2
1
Order By: Relevance
“…To further address this possibility and determine whether IGF-1-induced VEGF expression was solely HIF-1-dependent, we used CsA as an inhibitor of Hif-1␣ stability (D'Angelo et al, 2003). We observed that CsA treatment inhibited IGF-1-stimulated Hif-1␣ protein expression and HIF-1 reporter activity, at the same time only partially reducing VEGF secretion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To further address this possibility and determine whether IGF-1-induced VEGF expression was solely HIF-1-dependent, we used CsA as an inhibitor of Hif-1␣ stability (D'Angelo et al, 2003). We observed that CsA treatment inhibited IGF-1-stimulated Hif-1␣ protein expression and HIF-1 reporter activity, at the same time only partially reducing VEGF secretion.…”
Section: Discussionmentioning
confidence: 99%
“…CsA is a potent immunosuppressive agent that destabilizes Hif-1␣ by promoting hydroxylation of Pro-402 and Pro-564 within its oxygen-dependent degradation domain (D'Angelo et al, 2003). IGF-1 and CoCl 2 treatment each increased Hif-1␣ protein expression ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, it has been reported that infusion of CsA, a calcineurin/NFAT inhibitor, in rats during MCT-induced PAH decreases PA pressure and medial hypertrophy (4), which contradicts our observation that phenamil attenuates hypoxia-induced PAH and vascular remodeling by activating NFAT. It is known that CsA also inhibits the activity of hypoxia-inducible factor 1␣ (HIF-1␣), a transcription factor involved in hypoxia-mediated gene regulation (10). Thus, the therapeutic effect of CsA in a PAH animal model might be FIG.…”
Section: Discussionmentioning
confidence: 99%
“…The pCMV-ODD-GFP vector (encoding ODD-GFP) and pCMV-GFP are kind gifts from Dr. D'Angelo (Institut de Pharmacologie Moleculaire et Cellulaire du Centre National de la Recherche Scientifique, France; ref. 30). The ODD fragment corresponds to amino acids 530 to 603 of HIF-1a.…”
Section: Methodsmentioning
confidence: 99%